Community Participation in Running Government and as Members of the House of Representatives through General Elections in Indonesia - Rahayu, Panti (Law Research Review Quarterly, 2018)
Competition among political parties in large numbers causes the possibility of success to be smaller, hence coalition is the most rational choice. This situation resulted in the emergence of super tight contestation among coalition political parties. So that the main focus is to win the contestation with all efforts, and the intention to participate in the government and become a member of the House of Representatives even as if looking for work. The purpose of this paper is to provide an attitude and criticism of the community in this case who are incorporated in political parties about their role as representatives of the people in the government and as members of the House of Representatives obtained through general elections (elections). The writing method used is normative juridical by using the statutory approach and conceptual approach. The conclusion is that the community has the right to participate in running the Government as well as becoming a member of the House of Representatives through elections, but its rights must also be accompanied by a series of obligations that must be carried out with the main goal of public welfare in general, not the community members and groups. partisans of the political parties which are its aegis.